Avaliação do topmodel em microbacia hidrográfica no município de Alegre, ES - Hollanda, Maycon Patricio de (2012)
The unsustainable use of natural resources has generated conditions of scarcity or even exhaustion of some of these resources. Water is a natural resource most threatened by unsustainable exploration. The study watersheds enables integration of the factor